1988
DOI: 10.1016/0014-5793(88)80552-0
|View full text |Cite
|
Sign up to set email alerts
|

Electron transfer from A1to an iron‐sulfur center witht= 200 ns at room temperature in photosystem I Characterization by flash absorption spectroscopy

Abstract: Forward electron transfer in intact photosystem I particles from Synechococcus sp. at room temperature has been studied by flash absorption spectroscopy with a time resolution of 5 ns. A kinetic phase with I ,,2 = 200 ns was resolved and characterized by its absorption difference spectrum between 325 and 495 nm. This phase is attributed to electron transfer from the reduced redox center A, to an iron-sulfur center, probably F.. The difference spectrum for the reduction of A, is evaluated and the previously pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
80
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 27 publications
19
80
1
Order By: Relevance
“…The spectra of the two nanosecond phases were attributed to reoxidation of A 1 Ϫ . As previously observed in cyanobacteria (27) and Chlorella (13), the nanosecond phases displayed positive absorption in the 370-to 400-nm range, characteristic for semiphylloquinone, and contributions from the electrochromic band shifts induced by the presence of a charge on A 1 . The positive band at 480 nm has been attributed to a shift in the absorption spectrum of a carotenoid molecule in the close vicinity of the phylloquinone.…”
Section: Resultssupporting
confidence: 80%
“…The spectra of the two nanosecond phases were attributed to reoxidation of A 1 Ϫ . As previously observed in cyanobacteria (27) and Chlorella (13), the nanosecond phases displayed positive absorption in the 370-to 400-nm range, characteristic for semiphylloquinone, and contributions from the electrochromic band shifts induced by the presence of a charge on A 1 . The positive band at 480 nm has been attributed to a shift in the absorption spectrum of a carotenoid molecule in the close vicinity of the phylloquinone.…”
Section: Resultssupporting
confidence: 80%
“…4 left, circles) agrees well with P700F,,,/P700+F.& difference spectra reported for the same material [7] and for PS I from spinach [24]. spectrum of monomeric PS I (Fig.…”
Section: Electron Transfer In Ps I Core Complexessupporting
confidence: 81%
“…In both samples the initial (at t 2: 5 ns) absorption change due to the formation of P700'A; is fol- lowed by a kinetic phase with a half life of about 180 ns. This phase has been attributed to the electron transfer from A; to an iron-sulfur-center but it was not possible to clarify which of the iron-sulfur-centers accepts the electron, since the spectral properties of the FeS-centers are nearly identical [7]. For quantitative analysis of the kinetics, the relative size of the 180 ns component in both samples has been determined by fitting the data with one exponential plus a constant.…”
Section: Reoxidation Kinetics Of A;mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have indicated that the PS I reaction center contains two molecules of phylloquinone (= vitamin K1)/reaction center [8,9], one of which presumably functions as the primary electron acceptor A1 [10][11][12][13][14][15] and mediates electron transfer between the reduced electron acceptor intermediate, chlorophyll a (A~), and Fx the ironsulfur secondary electron acceptor. Some arguments against the function of phylloquinone, however, still remain ~ [16,17] and its binding site has not been well characterized.…”
Section: Introductionmentioning
confidence: 99%